HUBUNGAN KOMITMEN ORGANISASI DENGAN MOTIVASI KERJA KARYAWAN PT. JASAMARGA CABANG BELMERA - Siti Aisyah (Faculty of Psychology, Universitas Medan Area, 2015)
The aim of this research is to know relation between organizational commitment with workmotivation of employment of PT Jasa Marga branch Belmera Medan. There are 70 employmentused as sample in this research and different background as like education, and workexperience. The results show that there are no relation between organizational commitment andwork motivation, which coefficient correlation (rxy) = 0,037 and p > 0,05.